2003
DOI: 10.1093/qjmed/hcg108
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of hydrocephalus as a presenting feature of tuberculous meningitis

Abstract: Hydrocephalus upon presentation is common in our TBM patients. This may be a poor prognostic marker associated with severe TBM and a higher risk of stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 14 publications
2
30
0
Order By: Relevance
“…Vasospasm and ventricular dilatation may contribute to constriction of arteries already compromised by vasculitis. 9,13,21 After recovery from the acute illness, fibrosis around blood vessels in the subarachnoid space can cause late-onset infarcts. 8,10 Angiography typically shows focal narrowing of the arteries at the base of the brain, most commonly in the terminal portions of the internal carotid arteries and the proximal segments of the middle and anterior cerebral arteries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vasospasm and ventricular dilatation may contribute to constriction of arteries already compromised by vasculitis. 9,13,21 After recovery from the acute illness, fibrosis around blood vessels in the subarachnoid space can cause late-onset infarcts. 8,10 Angiography typically shows focal narrowing of the arteries at the base of the brain, most commonly in the terminal portions of the internal carotid arteries and the proximal segments of the middle and anterior cerebral arteries.…”
Section: Discussionmentioning
confidence: 99%
“…In some series hydrocephalus has predicted a poor outcome, 12 but surgical drainage does not consistently improve the long-term outcome. 21 Corticosteroids may reduce the number of patients with tuberculous meningitis who develop hydrocephalus. 14 Cranial neuropathies occurred in 29% of our patients and in 20% to 52% of patients with tuberculous meningitis in other series.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,6 Much data relating to the complications of TB meningitis, including tuberculoma, hydrocephalus, encephalomyelopathy, radiculomyelitis, and cranial nerve palsies have been reported. 1,2,[6][7][8][9] Cerebral infarction secondary to infection has also been reported as a complication of TB meningitis. Prevention or reduction of complications, particularly significant complications such as cerebral infarction, is the most challenging goal for providing quality patient care.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] However lower percentages were seen in a study conducted by Chan et al who found it in 29% of the cases. 11 Why is this hydrocephalus found higher in our study as compared to the ones with lower percentages, it might be the cut off value used in this study, which was quite on the lower side, that's why it reflected in a very higher number. And the other studies with similar percentages also had lower threshold to label it.…”
Section: Discussionmentioning
confidence: 57%